TGFβ+ small extracellular vesicles from head and neck squamous cell carcinoma cells reprogram macrophages towards a pro‐angiogenic phenotype. Issue 12 (20th December 2022) - Ludwig, Nils; Yerneni, Saigopalakrishna S.; Azambuja, Juliana H.; Pietrowska, Monika; Widłak, Piotr; Hinck, Cynthia S.; Głuszko, Alicja; Szczepański, Mirosław J.; Kärmer, Teresa; Kallinger, Isabella; Schulz, Daniela; Bauer, Richard J.; et al.
Abstract: Transforming growth factor β (TGFβ) is a major component of tumor‐derived small extracellular vesicles (TEX) in cancer patients. Mechanisms utilized by TGFβ + TEX to promote tumor growth and pro‐tumor activities in the tumor microenvironment (TME) are largely unknown. TEX produced by head and neck squamous cell carcinoma (HNSCC) cell lines carried TGFβ and angiogenesis‐promoting proteins. TGFβ + TEX stimulated macrophage chemotaxis without a notable M1/M2 phenotype shift and reprogrammed primary human macrophages to a pro‐angiogenic phenotype characterized by the upregulation of pro‐angiogenic factors and functions. In a murine basement membrane extract plug model, TGFβ + TEX promoted macrophage infiltration and vascularization ( p < 0.001), which was blocked by using the TGFβ ligand trap mRER ( p < 0.001). TGFβ + TEX injected into mice undergoing the 4‐nitroquinoline‐1‐oxide (4‐NQO)‐driven oral carcinogenesis promoted tumor angiogenesis ( p < 0.05), infiltration of M2‐like macrophages in the TME ( p < 0.05) and ultimately tumor progression ( p < 0.05). Inhibition of TGFβ signaling in TEX with mRER ameliorated these pro‐tumor activities. Silencing of TGFβ emerges as a critical step in suppressing pro‐angiogenic functions of TEX in HNSCC.